Clinicopathological study of oral lichen planus and oral linchenoid reaction / Eb Robson Gubod - Eb Robson, Gubod (2020)
Introduction: Oral lichen planus is a chronic inflammatory disease that affects the mucosa of the oral cavity. Oral lichenoid reactions/ lesions share many clinical and histopathological features with oral lichen planus, and represent a response to extrinsic or causative factors (drugs, allergens). Aim: The purpose of this study was to evaluate the clinical and histopathological features of oral lichen planus and oral lichenoid reactions/ lesions. Objectives: The objectives of this study were to assess the clinical and histopathological features of patients diagnosed with oral lichen planus and oral lichenoid reaction/ lesions. This study also sought to investigate the association between clinicopathological characteristics and patients with/ without exposure to causative factors. Finally, this study compared the ratio of plasma cells to lymphocytes in patients with/ without exposure to causative factors. Methods: This study was conducted in a retrospective manner in patients who have been diagnosed with oral lichen planus and oral lichenoid reaction/ lesions in Faculty of Dentistry, University of Malaya. A total of 122 patients that met the inclusion criteria were studied. Socio-demographic and clinical data for each case were obtained from clinical folders in Oral medicine clinic and histopathology reports in Oral Pathology Research and Diagnostic Laboratory (OPDRL). Histopathological data was extracted from the archived hematoxylin and eosin stained slides in OPDRL. Histopathological scoring of plasma cells and lymphocytes was done using 3D Histech and QuPath softwares. Data was analyzed using chi-square, logistic regression, and receiver operating curve analysis. Results: There were significant differences in plasma cells to lymphocytes ratio between patients who were exposed to causative factors and those who were not (p=0.043 and p=0.031). Plasma cells to lymphocytes ratio in patients exposed to causative factors was higher than those who were not (p=0.048 and p=0.032). Presence of eosinophils was significantly associated with exposure to causative factors (p=0.016 and p=0.011), deeper inflammatory infiltrate iv (p=0.016), and epithelial atrophy (p=0.043). Conclusion: This study demonstrated association between the presence of eosinophils and exposure to causative factors, which were consumption of medications that had been associated with oral lichenoid reaction, and also presence of restorative materials adjacent to lesions. Moreover, this study demonstrated higher plasma cells to lymphocytes ratio in patients exposed to causative factors than those who were not. These findings strongly support the role of causative factors, mainly the drugs and dental restorative materials in the etiology of oral lichenoid reactions/ lesions, although it is difficult to pinpoint. Thus, in clinical settings, together with proper history and clinical findings, these features may facilitate clinicians in planning appropriate management for patients.